Criminal Policy and The Role of The Government in The Control of Commercial Sex Workers in The District of Kuningan - Nanang Suhendar; Sri Kusriyah (Jurnal Daulat Hukum, 2018)
In Containment measures undertaken by the Local Government District of Kuningan to the presence of prostitutes is to use a penal policy that is with the issuance of Regulation No. 3 of 2015 on Public Order and Peace Society. These regulations are still too general and not specifically discuss countermeasures against prostitutes. Based on Regulation No. 3 of 2015, there are at least three agencies that have the authority and responsibility directly to the PSK reduction in Kuningan regency. All the three agencies including the Department of Social and Labor of Kuningan district. Kuningan regency and municipal Police District of Kuningan. The research is qualitative research in the form of descriptive analysis using sociological juridical approach. Prevention efforts refresif PSK only be done by way of a raid conducted by the municipal police and the Police of Kuningan. PSK is captured in the raid, was ordered to make a statement and then forced the release back. This is done because the Department of Social Welfare and Labor as the institution in charge to distribute PSK to rehab in palimanan not receive distribution PSK. This happens because of a rehabilitation center in palimanan quota is full and PSK for Kuningan district just 10 people. Related Bylaw PSK reduction should be set so that preventive efforts can be carried out preventive and repressive.Keywords: Criminal Policy; Commercial Sex Workers; Local Government.